Analisis Profitabilitas Broiler Pola Kemitraan Di Desa Kembuan Kecamatan Tondano Utara Kabupaten Minahasa - Oroh, Frangky Stanly; Tarigan, Abel. P.; Pandey, Jeane (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
This study aims to analyze production costs, revenues and income as well as analyze the level of profitability and R/C ratio in the broiler business in Kembuan Village, North Tondano District, Minahasa Regency. This research was carried out during the months from December 2021 to January 2022. This research was carried out using a survey method with a case study method. The research was conducted on a partnership pattern broiler farm owned by Mr. Marcel Lemo based on his consideration as a broiler breeder who has been experienced in raising broilers Â for 20 years and a livestock population of Â 5000 heads in North Tondano District. Based on the results of the research and analysis results, the income obtained by the partnership pattern broiler breeders in Kembuan Village per period, respectively, for the first period of Rp.15,240,461, the second period of Rp. 6,231,502 and the third period of Rp. 12,145,682. Profitability ratios obtained for each period are 7.82 for the first period, 3.36 for the second period and 6.98 for the third period, which means that this business is profitable and efficient, while the R/C ratio for the first and third periods is 1.07 and the second period is 1. ,03. This means that the broiler farming business is a profitable and feasible partnership to be developed.